Critical discourse analysis of online resistance against compulsory hijab law in facebook postings, Iran - Dehghan., Ehsan (2015)
Iran is one of the few countries in the world with laws of compulsory hijab for women,regardless of their religion. In the last couple of years, Iranian women have formed online communities to resist such laws and voice their dissent. The role of online social networks in causing social change, and the extent by which these New Media can help the process of democratization, has been a matter of increasing academic attention. However, there are not enough studies, particularly from a linguistics viewpoint, on the online resistance movement of Iranian women against compulsory hijab. This leaves a gap in our understanding of both the dynamics and strategies of such movements, and also the bigger question of whether or not New Media can be useful tools in advancing human rights, democracy, and equality. This study, employing the Discourse-Historical Approach to Critical Discourse Analysis, is an attempt to fill this gap by investigating a corpora consisting of over 500 Facebook posts by pages created for the purpose of resisting compulsory hijab in Iran. The findings of the study point to a strong dichotomization of Self and Others in the online Iranian discourse of hijab, in which the Self is comprised of Iranian women, while the Others are pro-state and procompulsory-hijab men. Using an array of social theories from sociology, psychology, philosophy, and feminism, it is discussed how the resistance movement under study is self-destructive, mainly due to the discourse participants’ lack of awareness of how the linguistic, discursive, and argumentative strategies employed reproduce the same ideologies the Iranian women are resisting.